(untitled) (Anclajes, 2024)
Since he began his solo career, Puerto Rican singer Enrique Martín Morales (1971-), known artistically as Ricky Martin, kept his private sphere away from the media. However, on March 29, 2010, and after several years of speculation by the press, he publicly accepted his homosexuality. In his autobiography, titled Me (2010), he outlines the process of internalizing his sexual orientation and subsequently announcing it through social media. In the context of the shame/pride binomial, the aim is to analyze the discourses of rejection/acceptance that underlie the autobiography and assess their meanings. Likewise, the obstacles that public figures who express dissident sexualities must face and the benefits that their coming out brings to society.